Characteristics of T- and NK-cell Lymphomas After Renal Transplantation: A French National Multicentric Cohort Study. Issue 8 (August 2021) - Barba, Thomas; Bachy, Emmanuel; Maarek, Alizée; Fossard, Gaëlle; Genestier, Laurent; Anglicheau, Dany; Moal, Valérie; Dantal, Jacques; Rieu, Philippe; Chemouny, Jonathan; Charrier, Manon; Durrbach, Antoine; et al.
Abstract : Background: Posttransplant lymphoproliferative disorders (PTLDs) encompass a spectrum of heterogeneous entities. Because the vast majority of cases PTLD arise from B cells, available data on PTLD of T or NK phenotype (T/NK-cell PTLD) are scarce, which limits the quality of the management of these patients. Methods: All adult cases of PTLD diagnosed in France were prospectively recorded in the national registry between 1998 and 2007. Crosschecking the registry data with 2 other independent national databases identified 58 cases of T/NK-cell PTLD. This cohort was then compared with (i) the 395 cases of B-cell PTLD from the registry, and of (ii) a cohort of 148 T/NK-cell lymphomas diagnosed in nontransplanted patients. Results: T/NK-cell PTLD occurred significantly later after transplantation and had a worse overall survival than B-cell PTLD. Two subtypes of T/NK-cell PTLD were distinguished: (i) cutaneous (28%) and (ii) systemic (72%), the latter being associated with a worse prognosis. Compared with T/NK-cell lymphomas of nontransplanted patients, overall survival of systemic T/NK-cell PTLD was worse (hazard ratio: 2.64 [1.76-3.94]; P < 0.00001). Conclusions: This difference, which persisted after adjustment on tumoral mass, histological subtype, and extension of the disease at diagnosis could be explained by the fact that transplanted patients were less intensively treated and responded less to chemotherapy.